First study of the radiation-amplitude zero in W gamma production and limits on anomalous WW gamma couplings at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Prosper, H. B.; et al. (Amer Physical Soc, 2008)
We present results from a study of p (p) over bar -> W gamma+X events utilizing data corresponding to 0.7 fb(-1) of integrated luminosity at root s = 1.96 TeV collected by the D0 detector at the Fermilab Tevatron Collider. We set limits on anomalous WW gamma couplings at the 95% C.L. The one-dimensional 95% C.L. limits are 0.49 <kappa(gamma)< 1.51 and -0.12 <lambda(gamma)< 0.13. We make the first study of the charge-signed rapidity difference between the lepton and the photon and find it to be indicative of the standard model radiation-amplitude zero in the W gamma system.